Food on display: design techniques of the food exhibits of the New York World's Fair of 1939-40. (15th March 2021) - Miller, Bonnie M.
ABSTRACT: This article examines how displays in the Food Zone of the New York World's Fair (1939–40) represented the future of food production, preparation, and consumption through the spectacular frameworks of art/aesthetics, performance, gastronomy, and scientific innovation. Industrial designer Russel Wright constructed the main thematic exhibit of the Food Zone, the Focal Exhibit. Bringing his experience as a stage designer to the project, he sought to convey a visual history of the human diet over the last 150 years through humor and surrealism. Using fair guidebooks, photographs, and publicity materials, this essay juxtaposes Wright's strategy to engage visitors through critical thinking with the techniques of commercial exhibits, like Borden's, the Continental Baking Company, and Heinz, who more directly showcased the making of and tasting of their products. While the Food Zone as a whole celebrated food processing for transforming the food industry, the different approaches that exhibitors took to communicate that message gives insight into cultural tensions over the meaning of food to consumers. Whereas the Food Focal Exhibit depicted food as elemental, an instrument of alimentation, some of the most successful exhibits celebrated the joys of cooking and eating, recognizing food's social and gastronomic functions in daily life.